Influence of Patient Related Factors on Health Seeking Behaviours among Men with Lower Urinary Tract Symptoms attending Surgical Out Patient Clinic at Meru Level Five Hospital, Kenya - Muriuki, Festus Mwendia; Oluchina, Sherry; Mbithi, Bernard Wambua; Kirigia, Consolata (Journal Of Nursing Practice, 2020)
Background: Currently there are increased cases of men presenting with Lower Urinary Tract Symptoms (LUTS) especially in low resource countries. These symptoms may or may not be related to prostate cancer and health seeking behaviours are not clear.   Purpose: To establish the influence of patient related factors on health seeking behaviours for Lower Urinary Tract Symptoms (LUTS) among men attending surgical outpatient clinic at Meru hospital, Kenya.Methods: Descriptive cross-sectional study design was used. The study population involved 120 men suffering from LUTS, 2 physicians and 2 nurses. Questionnaires and interview guides were used for data collection. Study period was from August 2018 to March 2020.Results: Majority (67.0%) of the patients with LUTS were aged between 61-70 years. Also, the majority (68.8%) of the respondents had primary level of education. The findings also pointed out majority (72.0%) of the patients were farmers with income level of below Ksh. 20,000. Logistic regression was used whereby P-values determine the statistical significance of results with cut off set at (p ?0.05). The inferential statistics pointed out that patient related factors test items had a statistical significant influence since the p-values were found to be less than 0.05 at 95% confidence interval. Conclusion: There was a significant negative influence of patient related factors such as lack of knowledge, low income levels and distance to health care facilities on health seeking practices. Therefore patients seek medical attention when quality of their lives has been threatened. The study recommends adopting measures of rising awareness on need for seeking early medical attention and initiate outreach health services in underserved areas or through telehealth